(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This PVC manufacturing in the article release as a result harvest to be chlorinated from hydrocarbons adhesive tars synthesis to do opportunities studied. Research during chlorinated hydrocarbons, cyanide acid and urea-formaldehyde based on resin (KFS) glue working release method offer Synthesis process temperature, concentration and reaction duration such as to the parameters impact analysis Results this showed that the modified glue high adhesion to the ability has is different industry in the fields application possible.